Crisis and capitalism in contemporary Argentine cinema - Page, Joanna, 1974- (e-Duke books scholarly collection., 2009)
There has been a significant boom in recent Argentine cinema, with an explosion in the number of films made in the country since the mid-1990s. Many of these productions have been highly acclaimed by critics in Argentina and internationally. What makes this boom all the more extraordinary is that it has coincided with a period of severe economic crisis and civil unrest in the nation. Offering the first in-depth English-language study of Argentine fiction films released since the mid-1990s, Joanna Page explains how these productions have registered Argentina's experience of capitalism, neo-liberalism, and economic crisis. In different ways, the films selected for discussion testify to the social consequences of growing unemployment, rising crime, marginalization, and the expansion of the informal economy. Page focuses particularly on films associated with New Argentine Cinema, but she also discusses highly experimental films and genre movies borrowing from the conventions of crime thrillers, Westerns, and film noir. She analyzes films that have received wide international recognition alongside others that have rarely been shown outside Argentina.